Pemanfaatan Limbah Rumah Tangga Minyak Jelantah Di Desa Jatibaru 2, Tanjung Bintang - Nida Lidya Susanti; Salman Farisi; Suratman; Bambang Irawan; Devi Eka Lestari (CV. Multi Kreasi Media, 2026)
Used cooking oil is a type of domestic waste that has the potential to cause adverse impacts on both health and the environment if not properly managed. This community service activity aimed to enhance the community’s understanding and capacity to process used cooking oil waste into valuable products. The activity was conducted on January 30, 2026, in Jatibaru 2 Village, Tanjung Bintang District, South Lampung Regency, involving 30 participants involving a group of housewives and young women. The methods used included lectures, hands-on practice, and interactive discussions. The results of the activity indicated an improvement in participants’ understanding, as reflected by an increase in the average score from 6 in the pre-test to 8 in the post-test. In addition, participants demonstrated high enthusiasm and were able to process used cooking oil into economically valuable products. This activity not only increased community awareness of proper waste management but also created opportunities for small-scale business development based on household waste utilization. Therefore, this activity contributes to environmental conservation efforts while simultaneously strengthening sustainable community economic empowerment.